2022
DOI: 10.15566/cjgh.v9i1.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local faith-actor engagement in the uptake and coverage of immunization in low- and middle-income countries: A literature review

Abstract: Introduction: Religious leaders are universally recognized as having an influence on immunization uptake and coverage in low- and middle-income countries (LMICs). Despite this, there is limited understanding of three questions: 1) how do religious leaders impact the uptake and coverage of immunization in LMICs? 2) what successful strategies exist for working with local faith actors to improve immunization acceptance? and 3) what evidence gaps exist in relation to faith engagement and immunization? Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Particularly in relation to COVID-19 vaccination, the importance of collaboration with religious leaders and multi-sectoral partnerships is important in reducing hesitancy and work toward the shared goal of building public trust in vaccines ( 37 ). A systematic review published in May 2022 found mixed evidence that religious leaders can both promote vaccination and inhibit vaccination, suggesting the need to engage religious leaders more effectively ( 38 ). Another study in 22 countries across Europe showed that in countries where the majority religious group had a leader who publicly and consistently supported vaccination against COVID-19, religiosity was positively related to vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in relation to COVID-19 vaccination, the importance of collaboration with religious leaders and multi-sectoral partnerships is important in reducing hesitancy and work toward the shared goal of building public trust in vaccines ( 37 ). A systematic review published in May 2022 found mixed evidence that religious leaders can both promote vaccination and inhibit vaccination, suggesting the need to engage religious leaders more effectively ( 38 ). Another study in 22 countries across Europe showed that in countries where the majority religious group had a leader who publicly and consistently supported vaccination against COVID-19, religiosity was positively related to vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Yendell, O. Hidalgo, C. Hillenbrand 2021: 100 ff.]. Faith actor engagement can become a gamechanger in the fight for immunization in low-income countries [Melillo et al, 2021]. Interreligious dialogue can give a powerful contribution in strengthening cooperation and combating discrimination in "fragile contexts" (Holden 2021).…”
Section: Concluding Remarks: a Lesson From The Pandemicmentioning
confidence: 99%
“…Traditionally, reviews on PHA-FBO partnerships to increase vaccine confidence and uptake have focused on interventions in LMICs 28–31. Olivier and colleagues from the Joint Learning Initiative on Faith and Local Communities published a comprehensive report and a journal publication looking at 43 examples of faith community participation in immunisation programmes in LMICs 29 30.…”
Section: Introductionmentioning
confidence: 99%
“…Another review conducted by the Faith Engagement Team of the US Agency for International Development’s MOMENTUM Country and Global Leadership programme, collected 110 studies on evidence of local faith actors’ influence on community vaccine hesitancy28. Its most recent review described PHA-FBO partnership strategies that may improve COVID-19 vaccine confidence in 4 sub-Saharan countries 31. Besides written reviews, conferences and panel sessions hosted by the WHO, UNICEF and Global Alliance for Vaccines and Immunisation (GAVI) offered collaborative opportunities for FBOs to share how PHA-FBO partnerships increase vaccine confidence and uptake in the context of LMICs; and open dialogues on issues of governance in equitable distribution 32–34…”
Section: Introductionmentioning
confidence: 99%